The End of the Dream of Unity - Labarca, Martín Gabriel (2008)
The dream of the logical-positivism of the beginning of the 20th century was the unity of sciences, according to which all scientific disciplines could be explained by means of the laws of fundamental physics. In this reductionist context, physics was at the top in the hierarchy of natural sciences due to its fundamental character whereas chemistry was relegated to an inferior position to the extent that it was supposedly derived from quantum physics. However, at the beginning of this century it is possible to stress that chemistry is neither a reduced science nor a branch of physics.